Requirements for Badminton Strokes in One Game by Elite Athletes in Single Match Numbers - Adi, Indra Kusuma; Kristiyanto, Agus; Nugroho, Haris (Quality in Sport, 2022)
Badminton is experiencing rapid development both domestically and abroad. The ultimate goal of this game is to try to drop the shuttlecock in the opponent’s playing area and try to prevent the opponent from hitting the shuttlecock and dropping it on his own court, if the shuttlecock falls on the floor or gets stuck in the net, the game stops. The purpose of this study was to analyze Requirements for Badminton Strokes in One Game by Elite Athletes in Single Match Numbers. The researchers used a one-shot case study design. This research was carried out by observing badminton match videos that were broadcast on the internet media, namely YouTube. In this study, observers analyzed 4 matches played by single athletes ranked in the top 10 in the world. The data that has been collected is then analyzed, while the technique used is the percentage. Based on the results of the study, it can be concluded that the average results of each badminton Elite Athletes’ stroke in Single Match Numbers in One Game, namely: Service 10.20%, Chop 4.86%, Dropshoot 6.37%, Smash 12.21%, Lob 7.59%, Netting 33.08%, Drive 4.98%, Clear Lob 20.72%.The highest percentage is on badminton netting with a percentage result of 33.08%.